Bridging urban-rural disparities in malaria care during pregnancy in Senegal: evidence from household and health facility surveys - Yongsheng Jiang; Di Liang; Jinkou Zhao; Shailendra Prasad; Medoune Ndiop; Serigne Amdy Thiam; Ibrahima Diallo; Doudou Sene; Rose Mpembeni; Jiayan Huang (Infectious Diseases of Poverty)
Abstract Background Despite the World Health Organization’s recommendations, the uptake of Intermittent Preventive Treatment in pregnancy with sulfadoxine-pyrimethamine (IPTp-SP) in Senegal remains suboptimal, with disparities observed between urban and rural areas. More remains to be known about how malaria service readiness would affect the utilization of IPTp-SP. Methods Data were obtained from seven annual rounds of Demographic and Health Surveys (DHS) and Service Provision Assessments (SPA) in Senegal from 2012 to 2019. Using sample domain linkage to link the databases at the regional level. A malaria service readiness index was calculated to quantify the malaria service delivery capacity within the service environment where women reside. The Heckman selection model was utilized to analyze the relationship between malaria service readiness and IPTp-SP utilization. Results From 2012 to 2019, the average number of IPTp-SP doses received in Senegal was 1.66 (95% CI: 1.65–1.68), higher in urban areas [1.73 (95% CI: 1.71–1.75)] than rural areas [1.63 (95% CI: 1.62–1.65)]. Each one-point increase in malaria service readiness led to a rise of 0.251 doses in IPTp-SP. The significant interaction (Coef. = − 0.523, P < 0.001) indicated that women in rural areas received fewer doses of IPTp-SP (0.089) than in urban areas (0.612) for every unit increase in malaria service readiness. Conclusions Linking household and health facility surveys revealed significant room for improvement in malaria service readiness and IPTp-SP utilization in rural areas in Senegal. For better IPTp-SP coverage, differential strategies are required for urban and rural settings. Urban areas need to enhance malaria service readiness, while rural areas should focus on improving service readiness alongside infrastructure and community engagement to bridge the urban-rural disparities. Graphical abstract